Attentional Capture and Ethical Responsibility in Theravāda Abhidhamma: A Formal Reconstruction of the Cognitive Sequence - Karunanayaka, Indrajith P. (Journal of International Buddhist Studies, 2026)
Understanding how intention and karmic accumulation occur within Buddhist ethics benefits from examining the cognitive sequence (citta-vīthi) described in Theravāda Abhidhamma. Standard manuals describe this process for isolated stimuli, but leave open how competing or overlapping objects are resolved under the system’s timing constraints. This paper introduces a typology of attentional capture based on four orthodox object-intensity categories: uninterrupted capture, delayed capture, weak capture, and mind-door capture. Using a formal reconstruction constrained by the one-consciousness-at-a-time rule, eka-citta (Buddhaghosa 1920, 96) and the seventeen-moment material lifespan (Nārada 1987, 237), it examines how attention is captured, delayed, or blocked under different conditions and traces the ethical significance of each outcome. The reconstruction suggests that delayed capture may weaken the conditions for wholesome volition through psychological momentum (the repetition condition, āsevana paccaya; Paṭṭhāna, Paccayaniddesa §12), that weak objects may never reach the volitional phase of impulsion (javana; Nārada 1987, 237–38), and that mind-door objects reach volitionally relevant processing with very little temporal buffer (Bodhi 2007, 143). By distinguishing how serial processing, object intensity, and temporal delay shape the path to volition, the study clarifies how these structural factors condition moral responsiveness without reducing ethics to mechanics. Across these modes, the analysis points to the determining moment (voṭṭhapana) as the site of moral conditioning rather than moral production: it sets the posture for the impulsion run that follows, while javana remains the locus of karmically productive volition.